2018
DOI: 10.4088/jcp.17m11611
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Late-Life Suicidal Behavior

Abstract: Objective Clinical heterogeneity is a key challenge to understanding suicidal risk, as different pathways to suicidal behavior are likely to exist. We aimed to identify such pathways by uncovering latent classes of late-life depression cases and relating them to prior and future suicidal behavior. Methods Data was collected from 09/2011-09/2015. We examined distinct associations of clinical and cognitive/decision-making factors with suicidal behavior in 194 older (50+) non-demented, depressed, elderly; 57 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“… 2 ‘Late-life’ studies tend to include a wide age range, in some cases starting at age 50. 3 , 4 Also, older people are more likely than younger persons to die on their first suicide attempt, 5 and prospective studies that focus on suicide outcomes in the 75+ age group are sorely needed.…”
Section: Introductionmentioning
confidence: 99%
“… 2 ‘Late-life’ studies tend to include a wide age range, in some cases starting at age 50. 3 , 4 Also, older people are more likely than younger persons to die on their first suicide attempt, 5 and prospective studies that focus on suicide outcomes in the 75+ age group are sorely needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, self-esteem has been shown to be associated with geriatric depression symptoms [15] and prognosis [17]. Numerous studies have documented a strong positive correlation between CM and low self-esteem [36][37][38].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, self-esteem is associated with the clinical symptomatology and prognosis in geriatric depression. Indeed, firstly, it has been found that low self-esteem significantly increases the risk of suicidal behaviour [ 15 ]. Secondly, depressive symptoms are negatively correlated with self-esteem in this population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To explain high suicide rates in old age, 1 researchers typically invoke stressors of aging such as illness, disability, loss, and cognitive impairment. 2,3 By contrast, relatively little is known about the role of personality in late-life suicide. In younger people, personality traits are among the strongest predictors of suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%